Knockout of farnesoid X receptor aggravates process of diabetic cardiomyopathy. (March 2020) - Qiang, Sujing; Tao, Lingyun; Zhou, Jie; Wang, Qianwan; Wang, Kesheng; Lu, Meiling; Wang, Weifeng; Han, Lin; Xue, Shaobo; Chen, Yan; Zhu, Huanhuan; Liu, Zheng; et al.
Abstract: Previous studies have shown that FXR is involved in glycolipid metabolism, tissue inflammation and regeneration in organs such as the liver, intestines and kidneys. Although FXR has been reported in cardiac tissue, its function in diabetic cardiomyopathy has not been reported. Here, we successfully constructed a diabetic mouse model of FXR −/− and evaluated the effects of FXR knockout on cardiac function in mice by measuring various indicators. We demonstrated that blood glucose levels in diabetic mice are significantly elevated in the case of FXR knockout. Our findings from cardiac ultrasound and tissue HE staining supported that FXR knockout aggravates diabetic cardiomyopathy. Masson staining of myocardial tissue and quantitative detection of α-SMA by qPCR suggest that FXR knockout exacerbates cardiac fibrosis in diabetic cardiomyopathy. Combined with the results of Oil Red staining and quantitative detection of triglycerides in fresh tissue blocks, we hypothesized that FXR knockout aggravates diabetes-induced cardiac lipid accumulation. Altogether our results revealed a role of the FXR in the diabetic cardiomyopathy, suggesting a possible novel target for the treatment of diabetic cardiomyopathy.